Ab initio computation for rational design of chemical receptor in sensor / Ahmad Nazmi bin Rosli - Rosli, Ahmad Nazmi (2014)
The advancement of computing power has greatly improved the application of computational chemistry for routine use in solving a wide variety of chemical problems. The once accurate but expensive methods such as Gn Theory and CCSD(T) calculation can now be completed within hours. The work presented here has utilized the power of computational chemistry to design the cation recognition molecules using carbonitrile functionality. The B3LYP with 6-31+g(d,p) and QZVP basis set had been verified and selected as the most appropriate methods to obtain optimized geometry and vibrational frequencies. The optimized geometries were later used to obtain Mulliken and CHELPG charges, GIAO nuclear magnetic shieldings, natural bonding orbitals (NBO) and overlap population (AOMix software). The accurate energies were obtained using composite Gn Theory methods (G3 and G4). The binding energies of unconjugated carbonitrile model (acetonitrile) with cations are showing a general trend of H+ > Be(II) > Mg(II) > Ca(II). Mg(II) is more strongly bound to acetonitrile by 33.3 kcal/mol compared to Ca(II). The carbonitrile-carboxaldehyde receptor models (2-cyano ethylene) had been employed to study the selectivity of Mg(II) against Ca(II) and examining the effects of keto-enol forms and negatively charged (enolate) sites. In both uncharged and anion forms, Mg(II) binds more strongly to the receptor model compared to Ca(II), by 55.1 and 30.3 kcal/mol, respectively. This study also includes three-dimensional design based on Ionomycin to elucidate interactions between the proposed receptor models with cations. The N and O terminals of 2-cyano ethanal enolate show comparable level of negative charge. The lack of charge disparity on the N and O terminals indicates efficient charge delocalization throughout the π-network that leads to stronger interactions. The unsaturated carbonitriles had also been studied using 2-cyano butadiene as Be(II) receptor. The terminal vinyl carbon in 2-CN BD rehybridizes from sp2 to sp3 with an increase of 7% of s character to allow interaction with Be(II) that leads to the formation of six-membered cyclic complex. Fabricated potentiometric chemical sensors with carbonitrile-doped sensing membrane had shown distinct signal patterns that can be exploited in sensor applications.